2021
DOI: 10.22452/mjcs.sp2021no1.1
|View full text |Cite
|
Sign up to set email alerts
|

Student Perception Study on Smart Campus: A Case Study on Higher Education Institution

Abstract: With the current development of science and technology, big data technology, the Internet of Things (IoT), cloud computing, and mobile Internet in Malaysia, it is time for smart campuses to be established and Higher Education Institution (HEI) should not have left behind. The smart campus is the upgraded version of a digital university, providing a better academic environment to the lecturers and students. A smart campus enhances education, research, design, and delivering the appropriate higher learning modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
1
0
1
Order By: Relevance
“…Mustafa et al [9] stated that the constant use of Information and Communication Technology (ICT), especially on smart campus projects, has been shown to affect students' health throughout the learning process. For example, research focusing on the impacts on lecturers found that exposure to virtual education might have unintended repercussions for students [10].…”
Section: A Health-related Issuesmentioning
confidence: 99%
“…Mustafa et al [9] stated that the constant use of Information and Communication Technology (ICT), especially on smart campus projects, has been shown to affect students' health throughout the learning process. For example, research focusing on the impacts on lecturers found that exposure to virtual education might have unintended repercussions for students [10].…”
Section: A Health-related Issuesmentioning
confidence: 99%
“…Campus inteligente pode ser entendido como uma área de pesquisa interessante, nova e emergente, em que se usa tecnologia e infraestrutura para apoiar e melhorar os processos e os serviços do campus, no ensino, na aprendizagem e na pesquisa (Tian et al, 2018). Seu principal objetivo é fornecer um melhor ambiente acadêmico para alunos e professores (Mustafa et al, 2021).…”
Section: Introductionunclassified